An Assessment of Plate Fixation in Traumatic Injuries of Pubic Symphysis (Journal of Pakistan Orthopaedic Association, 2017)
ABSTRACTObjective: the functional and radiological outcomes after plate fixation of pubic symphysis diastasisMethods: This was a retrospective study conducted from January 2012 to January 2016. A predesigned score was used to assess the functional outcome of patients and for radiological outcome, x-ray of pelvis taken at 12 months post operatively was analyzed and compared with the immediate post-operative x-ray.Results: 22 patients were enrolled in study with mean age 42.2 years (range 18-68).Population standard deviation was 9.57. Of these 20(91%) were males and 2(9%) were females. 04 (18.2%) patients had excellent, 13(59%) patients had good, 4 (18.2%) had fair and 1 (4.5%) had poor functional outcome. 11 (50%) patients had good radiological outcomes.Conclusion: Plate fixation of traumatic pubic symphysis diastasis with single or dual plating had given better results and early functional recovery.